ABOUT THE POSSIBILITIES AND CONDITIONS OF THE ALTERNATIVE GAS SUPPLY OF UKRAINE’S ECONOMY - Кісь, Святослав; Петренко, Віктор; Люта, Наталія (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
Based on the analysis of the situation with the provision of the national economy of Ukraine with natural gas, the article proposes to support the previously launched project on coal gasification and take the necessary steps in its scientific, technological and organizational support. It is emphasized that in the conditions of energy shortage, in particular, natural gas, representatives of the management of the energy sector of Ukraine need to pay attention to previously proposed, economically and technologically sound projects related to alternative gas supply to the economy. The authors of the article see the main problem of their implementation in modern conditions in the lack of proper interaction between the state, business, science and civil society, which would speed up processes and harmonize the interests of all stakeholders with further socio-economic efficiency. Based on the analysis of the resource potential of the Ukrainian coal industry, the possibility and expediency of using coal gasification technology as one of the alternatives for gas supply to the needs of the economy and the population has been proved. At the same time, the authors of the article emphasize that Ukraine already has experience in preparing projects related to gas production using coal combustion technology. Thus, in 2014, a subsidiary company «Gas of Ukraine», with the potential and pre-documented support of foreign creditors, demonstrates its readiness to conduct pre-project work. According to the authors of the article, the works were suspended for unreasonable reasons, based on the lack of vision and understanding of new approaches to the organization of innovation processes in the energy sector. In order to achieve further positive results in the field of alternative gas supply of Ukraine, avoiding scenarios in 2014, the authors propose to implement innovative projects in the field of energy supply taking into account the well-known model of Itzkowitz-Leidesdorf «triple helix». At the same time, it is advisable to use this model in an improved form, taking into account the participation of the fourth mandatory component - civil society. As a proposal for further active action in the field of alternative gas supply in the country, the article recommends starting work on the document «Program to assist Ukraine's national economy in replacing Russian gas», using the approach of the stakeholder interaction model of national projects. The final recommendations of the authors provide for a radical transformation of the channels of interaction between government, business, science and civil society, the creation of coordination councils with the participation of all stakeholders, as well as ensuring maximum publicity of their actions.